Herb Use Behavior for Long COVID Care among People in Ang Sila Sub-district, Mueang Chonburi District, Chon Buri Province - Sinwat, Suratsawadee; Jangjaroun, Kranthida; Kuan, Kitti (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Herbs are regarded as a viable option for disease prevention and treatment, and they are widely used in modern medicine and dietary supplements. The advantage of employing herbs as a medicine is that children have been taught this skill by their ancestors. The objectives of this study were to investigate the problems encountered by people in the Ang Sila Sub-district who used herbs in managing Long COVID symptoms and herb use behavior for Long COVID care in 20 people. Methodology: In this study, the qualitative research methodology was used. The data was collected using structured interviews, unstructured interviews, and observation forms developed by the researchers. The data analysis was performed using descriptive statistics. Results: According to the study of herb use behavior among the sample, it was found that the sample had correct basic knowledge about the use of herbs in alleviating Long COVID symptoms. They gained this knowledge from researching and searching for information through online media. This made herbs play a role in primary health care for the people of Ang Sila Sub-district, especially during the COVID-19 pandemic. This was because herbs are widely available and inexpensive. As for the situation and problems of the use of herbs, it was found that online media often provides false information, frequently exaggerating how beneficial they are, which encourages people to use herbs regularly. Conclusion: The study of herb use behavior for Long COVID care showed that the sample had basic knowledge about using herbs. However, they had incorrect herb use behavior and had incomplete information and knowledge.